2012
DOI: 10.1007/s13238-012-2055-0
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs: a new ray of hope for diabetes mellitus

Abstract: Diabetes mellitus has become one of the most common chronic diseases, thereby posing a major challenge to global health. Characterized by high levels of blood glucose (hyperglycemia), diabetes usually results from a loss of insulin-producing β-cells in the pancreas, leading to a deficiency of insulin (type 1 diabetes), or loss of insulin sensitivity (type 2 diabetes). Both types of diabetes have serious secondary complications, such as microvascular abnormalities, cardiovascular dysfunction, and kidney failure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 70 publications
(115 reference statements)
1
45
0
1
Order By: Relevance
“…Recently, a growing number of studies have revealed that microRNAs (miRNAs) function as genomic regulators, playing critical roles in various physiological processes, including glucose homeostasis and the pathogenesis of type 2 diabetes (T2DM) [5,6]. miRNAs are endogenous, small noncoding RNA molecules approximately 20 nucleotides in length that regulate gene expression posttranscriptionally by pairing to the 3 0 -untranslated region (3 0 UTR) of target gene mRNAs to suppress translation or induce mRNA degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a growing number of studies have revealed that microRNAs (miRNAs) function as genomic regulators, playing critical roles in various physiological processes, including glucose homeostasis and the pathogenesis of type 2 diabetes (T2DM) [5,6]. miRNAs are endogenous, small noncoding RNA molecules approximately 20 nucleotides in length that regulate gene expression posttranscriptionally by pairing to the 3 0 -untranslated region (3 0 UTR) of target gene mRNAs to suppress translation or induce mRNA degradation.…”
Section: Introductionmentioning
confidence: 99%
“…In case of mammals, imperfect base pairing between the miRNA guide strand and the mRNA target may lead to either target mRNA degradation and/or inhibition of protein synthesis [53]. Recent data suggest that miRNAs play a direct role in insulin secretion, pancreatic islet development and pancreatic β-cell differentiation; and indirectly control glucose and lipid metabolism, and are involved in secondary complications associated with diabetes [2]. Interestingly, a conditional knockout of Dicer 1, the sole Dicer enzyme responsible for the biogenesis of miRNAs in humans and mice, led to gross defects in all pancreatic lineages in mice emphasizing the role of miRNAs in diabetes [54].…”
Section: Biogenesis Of Mirnasmentioning
confidence: 99%
“…Based on the above observations, biofluids like serum and plasma can be stored at -20 or -80°C without substantial degradation of miRNAs. In addition to this, the availability of simple and sensitive approaches for characterization and quantitation of miRNAs (discussed above) make them suitable biomarkers for detection of many diseases [2,14].…”
Section: Animal Models Of T2dm: Identification Of Mirnas Linked Withmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also involved in the increase in β-cell mass in response to insulin resistance [7,8]. In patients with T1DM and T2DM, the expression profile of miRNA in the β-cell and in insulin sensitive tissues is altered [9][10][11]. In an animal model of T1DM, the NOD mouse, several miRNAs, including miR-21, miR-34a, miR-29 and miR-146a, are increased in the pre-diabetic state [12,13].…”
Section: Pathogenesis Of Diabetes and Mirnamentioning
confidence: 99%